Language didactics and communication: research field and teacher training - Calderón, Dora Inés (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The article provides arguments for proposing language didactics as a field of study that belongs to a wider field: language pedagogy. The first argumentation is addressed on the basis of the problems identified for research. The latter presents what constitutes a training component for teachers in this area. Three questions concerning knowledge construction in didactical training of teachers of language and communication (LaC) were considered: (1) What is the aim of research in language didactics? (2) What are the common topics of research in this field? (3) What are the challenges identified in research of this kind? The answers reveal that a didactic-type knowledge must be included as a fundamental know-how in the knowledge of teachers of LaC.